A narrative account of legislated social security changes for Germany - Sebastian Gechert; Christoph Paetz; Paloma Villanueva (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2016)
Exploiting official historical records of the German Bundestag and Bundesrat, the Federal Ministry of Labour and Social Affairs and the German statutory pension insurance scheme, we construct a narrative of legislated social security changes for Germany between 1970 and 2013 in order to identify important discretionary shocks to the social security system. The historical account covers major changes in transfers and social security benefits and contributions for pensions, health care, long-term care and unemployment insurance on the German federal level and thus complements the tax narrative of Uhl (2013). Based on the provided information we are able to code a rich bottom-up time-series of fiscal policy shocks for empirical macroeconomic analysis, addressing the identification problem. Therefore, we collect information regarding the underlying motivation, the dates of the legislative process and the prospective financial impact, closely following the methodology of Romer and Romer (2010) and Uhl (2013). – – Anhand von offiziellen historischen Informationen des Deutschen Bundestags und Bundesrats, des Bundesministerium für Arbeit und Soziales, sowie der Deutschen Rentenversicherung erstellen wir einen umfangreichen narrativen Datensatz von Änderungen in der Sozialgesetzgebung Deutschlands zwischen 1970 und 2013. Wir kodieren die zugrundeliegende Motivationen, Zeitpunkte des Gesetzgebungsverfahrens und die potenziellen finanziellen Auswirkungen. Unser Datensatz beinhaltet wesentliche Änderungen bei Leistungen, Transfers und Beiträgen in der Renten-, Kranken-, Pflege-, sowie Arbeitslosenversicherung und Sozialhilfe auf Bundesebene und ergänzt damit den Datensatz von Uhl (2013) zu Steuerrechtsänderungen. Mit den Daten erstellen wir eine Bottom-up-Zeitreihe wesentlicher diskretionärer finanzpolitischer Schocks des Nettotransfersystems für empirische makroökonomische Analysen, um das Identifikationsproblem zu adressieren. Wir folgen im Wesentlichen der Vorgehensweise von Romer und Romer (2010), und Uhl (2013).
urn:nbn:de:101:1-20160614753
Keywords: E62; H20; H30; H55; N00; 330; Narrative Record Identification; Action-Based Approach; Social Security